Implementasi dan Tantangan Kebijakan Kurikulum Merdeka Belajar Kampus Merdeka di Perguruan Tinggi Indonesia - Khotimah, Khusnul; Susanti, Ari Indra (Cetta: Jurnal Ilmu Pendidikan, 2025)
The Ministry of Education, Culture, Research, and Technology has established a new policy, namely Merdeka Belajar Kampus Merdeka Curriculum (MBKM). However, the implementation of Merdeka Belajar Kampus Merdeka (MBKM) is not always smooth across higher education institutions. This article aims to explore how this curriculum is implemented and what challenges are encountered in its implementation. The researcher uses a narrative review by outlining findings from 12 related studies sourced from Google Scholar, Researchgate, and Semantic Scholar. The research findings indicate that the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) in higher education is influenced by curriculum flexibility, faculty participation, collaboration with the industrial sector and educational partners, as well as student participation. The challenges faced include curriculum adjustment, course conversion, online mentoring, limited infrastructure, collaboration with partners, limited funding, regulations, and a lack of information and support. In conclusion, the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) curriculum in higher education in Indonesia has the potential to improve the quality of higher education. However, further efforts are needed to overcome the various existing challenges.